Efektivitas Model Pembelajaran Berbasis Proyek Terhadap Kemampuan Pemecahan Masalah Bangun Datar Siswa Kelas Ⅳ Sekolah Dasar - Khurin In Ratnasari; Vannisa Aviana Melinda; Titin Nurhidayati; Akhmad Zaeni; Mufidatur Rohmah (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2026)
Students’ mathematical problem-solving skills regarding plane figures remain relatively low, primarily due to the use of conventional teaching methods that tend to be teacher-centered and focused on rote memorization. This situation results in students being unable to relate mathematical concepts to real-world situations and experiencing difficulties in solving problem-based questions. Therefore, an innovative, student-centered learning model is needed; one such model is Project-Based Learning (PjBL), which emphasizes active student engagement through contextual and collaborative projects. This study aims to analyze the effectiveness of implementing the PjBL model on the problem-solving skills of fourth-grade students in the geometry unit at MIMA 26 Al-Falah Sumberejo Ambulu Jember during the 2025/2026 academic year. This study employs a quantitative approach with a pretest-posttest design. Data collection techniques include observation, interviews, questionnaires, tests, and documentation. Data analysis was conducted using descriptive and inferential statistics, with a Paired T-Test performed using SPSS. The results indicate a significant improvement in students’ problem-solving skills following the implementation of PjBL, with a significance level of 0.000 < 0.05. This indicates a significant difference between pretest and posttest results. Additionally, interview and observation findings suggest that PjBL enhances students’ collaboration, communication, and active participation in learning. The discussion indicates that the PjBL model is effective in improving students’ ability to understand problems, implement solutions, and evaluate the validity of those solutions. Project-based learning encourages students to think critically, work collaboratively, and reflect on their work. Thus, PjBL has proven to be an effective learning model for enhancing elementary school students’ mathematical problem-solving skills.